2015
DOI: 10.1016/j.addbeh.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Flexible emotion-based decision-making behavior varies in current and former smokers

Abstract: The findings indicate that both current and former smokers display a suboptimal pattern of decision-making than non-smokers during the standard IGT. However, with respect to the ability to change behavior following reversed contingencies, former smokers are more similar to non-smokers than to current smokers. Former smokers were also more aware of the contingencies than current smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…A meta-analysis of studies on internet gaming disorder (IGD) showed that individuals with IGD exhibited significant hypoconnectivity within the DMN ( 29 ). Low mPFC-MTG connectivity may bias decision-making in smokers, leading to risky behavior and further drug use ( 30 ). Internal connectivity within the DMN can influence recall for the best action, including emotional responses to specific events and circumstances from past experiences ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of studies on internet gaming disorder (IGD) showed that individuals with IGD exhibited significant hypoconnectivity within the DMN ( 29 ). Low mPFC-MTG connectivity may bias decision-making in smokers, leading to risky behavior and further drug use ( 30 ). Internal connectivity within the DMN can influence recall for the best action, including emotional responses to specific events and circumstances from past experiences ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, relapses are common despite treatment, with cigarette-smoking cessation interventions showing limited success overall [ 2 , 3 ]. Within addiction research, the failure of smoking cessation has been mostly attributed to nicotine dependence [ 4 , 5 ] and its influence on a wide variety of cognitive domains [ 6 ], such as sensory processing [ 7 ], executive functioning [ 8 ], and memory [ 9 ], among others. In particular, subcortical regions of the brain have been implicated by research on substance abuse and dependence.…”
Section: Introductionmentioning
confidence: 99%